Factorise : x ( cube ) + y ( cube ) + z ( cube ) - 3xyz.

tell me fast friend's...

x3+y3+z3-3xyz=

 

[x+y+z][x2+y2+z2-xy-yz-zx]

this is identity 

  • 7
x+ y+ z- 3xyz = (x+y+z) (x+ y+ z-xy-yz-zx)
  • 6
185 a cube plus b cube plus c cube minus 15 ABC
  • -4
 x3 + y3 + z3 - 3xyz = ( x+ y+ z ) ( x2 + y2 + z2 + xy + yz  + zx )
  • -1
[x+y+z] [x×x+y×y+z×z−xy−yz−zx]
  • -1
x^3+y^3+z^3-3xyz==(x+y+z) (x^2+y^2+z^2-xy-yz-zx)
  • 2
Hope it helps:)... Don'tforget to like by just keeping ur finger on smile

  • 4
9cube-3cube-6cube
 
  • -1
Thanks
  • 0
(x+y+z)(x?+y?+z?-xy-yz-xz)
  • 1
What are you looking for?